2016
DOI: 10.1186/s12889-016-3237-0
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation and assessment of use of a large scale water filter and cookstove program in Rwanda

Abstract: BackgroundIn an effort to reduce the disease burden in rural Rwanda, decrease poverty associated with expenditures for fuel, and minimize the environmental impact on forests and greenhouse gases from inefficient combustion of biomass, the Rwanda Ministry of Health (MOH) partnered with DelAgua Health (DelAgua), a private social enterprise, to distribute and promote the use of improved cookstoves and advanced water filters to the poorest quarter of households (Ubudehe 1 and 2) nationally, beginning in Western Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Like other rural areas in different developing countries, biomass was the only fuel option in the community. Previous studies also reported that nearly all rural communities used biomass fuel for cooking [ 8 , 11 , 18 ]. However, our finding regarding not using charcoal as a fuel source by the community for either cooking or heating was inconsistent with other findings reporting its continuing use by many in rural communities [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other rural areas in different developing countries, biomass was the only fuel option in the community. Previous studies also reported that nearly all rural communities used biomass fuel for cooking [ 8 , 11 , 18 ]. However, our finding regarding not using charcoal as a fuel source by the community for either cooking or heating was inconsistent with other findings reporting its continuing use by many in rural communities [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been global and local initiates and interventions including The Global Alliance for Clean Cook Stoves, to alleviate the problem of HAP due to solid fuel by supporting adoption of clean and safe household cooking solutions [ 4 , 5 , 6 , 7 ]. However, different research findings indicate the existence of resistance to accept some technologies and/or failure of achieving the desired objective in preventing the health problems in some communities [ 5 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Repair and replacement of products is managed by DelAgua through district level facilities with problems being reported primarily through a dedicated call center phone line and communications with local officials. Further details of the delivery of the interventions and associated program activities are contained in a separate process evaluation paper [5] .…”
Section: Methodsmentioning
confidence: 99%
“…Coverage and use of household-level interventions are typically assessed using surveys and observations. However, a variety of studies have noted a poor correlation between self-reported and observed practices when evaluating the use of environmental interventions [70,72,91], and bias in self-reported outcomes is particularly likely when self-reported behaviors are perceived to be desired by evaluators or the wider community. The process of data collection itself can impact behavior, as individuals change their practices in response to the knowledge that they are being monitored, which is a phenomenon known as reactivity or the Hawthorne effect [92].…”
Section: Challenges Of Service Delivery Measurementmentioning
confidence: 99%